An analysis of soil disturbance from logging operation in a hill forest of Peninsular Malaysia - Jusoff, Kamaruzaman; Majid, Nik Muhamad (Elsevier Science, 1992)
This study was carried out to evaluate the extent and severity of soil disturbance that occurred in a typical harvesting operation in a Malaysian hill forest. A five-tier classification system described by Murphy (1982) was used to assess soil disturbance visually on the logging site for the one-month-old logging operation in a hill forest at Johol Forest Reserve, Negeri Sembilan, Malaysia. The three indices used were percentage of area with exposed mineral soil (AEMS), percentage of area with deep disturbance (ADD) and percentage of area undisturbed (AU). The study also evaluated the impacts of logging on soil physical properties. Soil samples were analysed for soil moisture content, total pore space, aeration porosity, available waterholding capacity, particle size analysis, bulk density, compressive strength and shear strength. From the study, the AEMS value was 14.6% and the ADD value was 10.1%. The total disturbed area was 23.1%. Results showed that all parameters used generally increased from ADD, AEMS and AU. All soil parameters measured, except for coarse sand, fine sand, bulk density, compressive strength and shear strength, showed significant decrease with increasing soil disturbance (DC0 to DC4). Coarse sand, fine sand, bulk density, compressive strength and shear strength showed a reverse pattern.